Non-invasive assessment of β-carotene levels in the skin of colombian adults (2012)
Introduction: Carotenoid pigments have antioxidant properties beneficial for human health. Use of resonance Raman spectroscopy (RRS) as a reliable method for measuring carotenoid levels in tissues such as dermis has been suggested. However, data about the variability and reproducibility of this technique should be collected before it can be used. Objective: To assess reproducibility of RRS for detection of total β-carotene levels in the skin of Colombian adults.